EFFECT OF SOLVENT AND EXTRACTION TIME VARIATION ON THE COFFEE OIL EXTRACTION RESULTS - Marisa Fitria; Rizka Mulyawan; Sulhatun Sulhatun; Agam Muarif; Syamsul Bahri (Chimica Didactica Acta, 2023)
The traditional coffee with the greatest taste is called arabica. One of the ingredients made from coffee beans and used for air freshener is coffee oil. The Soxhlet extraction method, a separation technique that is often used to separate one or more compounds from a solid or liquid by adding a solvent, is one of the processes for making coffee oil. This research has been done before, but a comparison of different types of solvents and inclusion of differences in extraction time has not been done. The purpose of this research is to understand how the difference in extraction time and the comparison of solvent types affect the yield, density, and acid number produced. Extraction of hexane and ethanol by distillation for 120 minutes is a research technique. Extraction times were 90, 120, 150 and 180 minutes. In this study, the largest extraction with ethanol solvent was produced within 120 minutes of 25.75%, while the highest percent yield of coffee oil with hexane solvent was obtained within 120 minutes of 17.3%. The maximum specific gravity for 180 minutes with ethanol solvent is 0.94 gr/ml, while for 180 minutes with hexane solvent is 0.91 g/mL. Coffee oil with hexane solvent produced an acid value between 3.2 and 7 mg KOH/g, while coffee oil with ethanol solvent produced an acid value between 4.6 and 11.2 mg KOH/g.